The use of ultrasound in clinical setting for children affected by NAFLD: is it safe and accurate? - Alisi Anna; Monti Lidia; Corte Claudia; Nobili Valerio; Feldstein Ariel (BMC, 2011)
Abstract Non-alcoholic fatty liver disease (NAFLD) has become over the last decade the most common form of chronic liver disease in children and adults. Thus, establishing the diagnosis of NAFLD is of utmost importance and represents a major challenge as the disease is generally silent and the current gold standard for diagnosis is an invasive liver biopsy, a procedure that is not suitable for screening purposes. Many non-invasive diagnostic tools have been evaluated so far. Recently the utility of ultrasonography for non-invasive diagnosis and estimation of hepatic steatosis has been demonstrated in a large prospective pediatric study.